UNVEILING THE VEIN - Marcel Ivanov; Charles Romanowski; Andrew Martin; Daniel Blackburn (Romanian Neurosurgery)
Cerebrospinal fluid (CSF)-venous fistula represents a formidable yet often overlooked neurosurgical dilemma. Despite its disabling consequences, it remains significantly underdiagnosed.